Human Cooperation in the Simultaneous and the Alternating Prisoner's Dilemma: Pavlov Versus Generous Tit-For-Tat - Wedekind, Claus; Milinski, Manfred (Proceedings of the National Academy of Sciences - PNAS, 1996)
The iterated Prisoner's Dilemma has become the paradigm for the evolution of cooperation among egoists. Since Axelrod's classic computer tournaments and Nowak and Sigmund's extensive simulations of evolution, we know that natural selection can favor cooperative strategies in the Prisoner's Dilemma. According to recent developments of theory the last champion strategy of ``win--stay, lose--shift'' (``Pavlov'') is the winner only if the players act simultaneously. In the more natural situation of players alternating the roles of donor and recipient a strategy of ``Generous Tit-for-Tat'' wins computer simulations of short-term memory strategies. We show here by experiments with humans that cooperation dominated in both the simultaneous and the alternating Prisoner's Dilemma. Subjects were consistent in their strategies: 30% adopted a Generous Tit-for-Tat-like strategy, whereas 70% used a Pavlovian strategy in both the alternating and the simultaneous game. As predicted for unconditional strategies, Pavlovian players appeared to be more successful in the simultaneous game whereas Generous Tit-for-Tat-like players achieved higher payoffs in the alternating game. However, the Pavlovian players were smarter than predicted: they suffered less from defectors and exploited cooperators more readily. Humans appear to cooperate either with a Generous Tit-for-Tat-like strategy or with a strategy that appreciates Pavlov's advantages but minimizes its handicaps.